PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA - Eriadi, Rizkie; Nugrahini, Dwi Setya (Jurnal Kewirausahaan dan Inovasi, 2023)
This study aims to determine the effect of the variables of motivation and job satisfaction on work discipline at the Tirta Benteng Regional Public Company, Tangerang city. The population of this quantitative associative type of research was 214 people and a sample of 140 people using the Taro Yamane formula which from the number of samples taken could describe the condition of the original population. This study uses quantitative data in the form of primary data sources with survey data collection techniques using questionnaires. This study used instrument tests through validity and reliability tests, classical assumption tests through normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests, and multiple linear regression analysis tests and hypothesis testing. The data analysis tool used is SPSS version 25. The results of the hypothesis show that the motivational variable has a significant effect on work discipline, the job satisfaction variable has a significant effect on work discipline, and the job satisfaction variable has a significant effect on work discipline.